Electrochemistry at the Nanoscale - Schmuki, Patrik; Virtanen, Sannakaisa (Nanostructure Science and Technology, 2009)
Electrochemistry at the Nanoscale contains theoretical and applied contributions on nanoelectrochemistry in a variety of fields of science and engineering, such as chemistry, physics, materials science, biology, and microtechnology. The book represents a compendium of recent developments and contains a toolbox of nanoelectrochemical principles and approaches.